PENINGKATAN HASIL BELAJAR IPA MATERI TUMBUHAN HIJAU MELALUI METODE EKSPERIMEN KELAS V SDN BABADAN SEMESTER 1 TAHUN PELAJARAN 2015/2016 - Masanah, Masanah (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2016)
The results of students of class V Semester Elementary School Babadan Bonang District of Demakdistrict in the academic year 2015/2016 on the subjects of Natural Sciences subject matter ofgreen plants is still low. This type of research used was classroom action research using modelexperiments. The study consisted of two cycles of the first cycle and the second cycle. Aftercarrying out repairs learning, student learning outcomes is increasing both the first cycle and thesecond cycle. For comparison, student achievement on pre cycle, students who completed theirstudy only 4 students, or 19%, 17 other students did not complete. On the improvement of learningfirst cycle, students who completed studies, has been increased to 13 from 21 students to 62%.Then after the second cycle of learning improvement obtained by students who pass the study asmany as 20 out of 21 students, or about 95%.